Heparanase inhibitor and antimetastasis: A mini-review of recent progress in cancer therapy and an Islamic perspective - Febriani, Ayu; Hafsan, Hafsan; Pratiwi, Afryanti; Ahmad, Arifuddin (Teknosains, 2026)
Heparanase is a critical enzyme involved in cancer metastasis through its role in degrading the extracellular matrix (ECM), which allows cancer cells to invade surrounding tissues and spread to distant organs. This mini-review explores recent advancements in understanding heparanase's function in cancer progression and the development of targeted therapies aimed at inhibiting its activity. Heparanase inhibitors, such as Roneparstat, have demonstrated significant potential in reducing tumor metastasis and improving the efficacy of existing treatments, including chemotherapy and immunotherapy. By altering the tumor microenvironment, these inhibitors enhance immune cell infiltration, improving response rates in otherwise resistant tumors. Additionally, heparanase has emerged as a promising biomarker for early cancer detection and prognosis, offering a new dimension to personalized treatment approaches. The review also incorporates an Islamic ethical perspective, emphasizing the obligation to preserve life and alleviate suffering through medical innovation. Continued research in this field is essential to refine therapeutic strategies and improve outcomes, particularly in cancers with high metastatic potential.